Ekstraksi Informasi Penutup Lahan Daerah Kabupaten Tanah Datar - M. Natsir (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2009)
Observation of land cover in Tanah datar Region has been conducted by using Landsat 7 ETM+path/row 127/60 acquired in 18 May 2002. The land cover can be differed into 7 (seven) classes. Most ofTanah Datar land is covered by forest, the first class. The second land cover area is padi field (sawah)that very difficult to be detected because of their different grow phases. The third, forth, fivth and sixthrespectively are dry agriculture area, plantation, mixed garden and residential area. Then, the lastclasses are lake and fish ponds.Kata Kunci: penutup lahan (land cover), penginderaan jauh (remote sensing), klasifikasi